Analisis Kesalahan Siswa Kelas VIII SMP Pada Materi Aljabar serta Proses Scaffolding-nya - Annisa Nur Ramadhani (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2016)
This study aimed to describe the 8th grader students’ mistake while working on algebra, the causes of the mistake, and the appropriate process of scaffolding to help the student realize his mistake. The researcher gave the test about algebra to all students on class A and class B to select the subject. After the subjects’ answers were analyzed, they were given the scaffolding and interviewed. The researcher found that the errors students did are in understanding the meaning of variables, carrying out the procedure, and the solving linear equations of one variable. Commonly, students’ mistake were caused by a failure in relating the problems with previous material and the lack of mastering basic arithmetic. To help the subjects realizing their mistake, researcher gave scaffolding level 2, that is reviewing and restructuring.Keywords: error analysis, algebra, scaffolding